1993
DOI: 10.1063/1.1143935
|View full text |Cite
|
Sign up to set email alerts
|

A noncontacting magnetostrictive strain sensor

Abstract: The operation of a noncontacting magnetostrictive strain sensor (NMASS) is verified experimentally. The sensor has a single excitation and a single detection coil, and utilizes the magnetostrictive effect. The magnetostrictive sensor offers noninvasive strain measurements on ferromagnetic materials with an accuracy comparable to conventional strain gages. The NMASS produces significantly more output compared to strain gages and holds promise for development into a generic strain sensor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…where the transformed stiffnesses Q ij are calculated from the plane stress-reduced stiffnesses, T is temperature rise, 1 , 2 , and 6 are the transformed thermal expansion coefficients, and e ij are the transformed magnetostrictive coupling moduli: 1 = 1 cos 2 + 2 sin 2 , 2 = 1 sin 2 + 2 cos 2 , …”
Section: Constitutive Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…where the transformed stiffnesses Q ij are calculated from the plane stress-reduced stiffnesses, T is temperature rise, 1 , 2 , and 6 are the transformed thermal expansion coefficients, and e ij are the transformed magnetostrictive coupling moduli: 1 = 1 cos 2 + 2 sin 2 , 2 = 1 sin 2 + 2 cos 2 , …”
Section: Constitutive Relationsmentioning
confidence: 99%
“…In particular, it has easy embedability into host materials without significantly affecting the structural integrity. Magnetostrictive material produces strains up to 2500 m, which is 10 times more than a piezoceramic material [5,6]. It also has high energy density, negligible weight, and point excitation with a wide frequency bandwidth [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The apparatus needed to excite the Terfenol-D and cause the boundary conditions to interact with the magnetic properties must be done through a magnetic field to nondestructively monitor the laminate. Kleinke and Uras developed a noncontacting magnetostrictive strain sensor (NMASS) which allows strain to be induced into a ferromagnetic element that is part of the flux path (Kleinke and Uras 1993). Their results showed that NMASS can be used to detect variations in the strain of the ferromagnetic element, by putting it in tension to produce a linear increase in the normalized output voltage (Kleinke and Uras 1993).…”
Section: Introductionmentioning
confidence: 96%
“…Kleinke and Uras developed a noncontacting magnetostrictive strain sensor (NMASS) which allows strain to be induced into a ferromagnetic element that is part of the flux path (Kleinke and Uras 1993). Their results showed that NMASS can be used to detect variations in the strain of the ferromagnetic element, by putting it in tension to produce a linear increase in the normalized output voltage (Kleinke and Uras 1993). Myers, and Anjanappa experimentally explored the concept of smart structures by embedding magnetostrictive particles in a Alplex and CFRP reinforced polymer laminates to find internal flaws of embedded different sized delamination patches using same concept of NMASS to sense delaminations (Myers 1996), (Myers and Anjanappa 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Among their various applications, the excitation and sensing of ultrasonic waves are the most notable from the viewpoint of a noncontact characteristic [1,6,7]. Especially the ultrasonic waves transmitted along a shaft contain a great deal of useful information on the defects or surroundings of the shaft.…”
Section: Introductionmentioning
confidence: 99%